Pengaruh gaya hidup Hedonis, flash sale, dan E-Payment terhadap perilaku Impulsive Buying pada mahasiswa Universitas Jambi dalam Perspektif Ekonomi Islam - Cindy Clarita Sari; Rafiqi .; Muhammad Roihan (JOURNAL OF SHARIA ECONOMICS, 2024)
This research aims to analyze the influence of hedonistic lifestyle, flash sales, and e-payment on the impulsive buying behavior of e-commerce users among students at the University of Jambi from an Islamic economic perspective. This study uses a quantitative approach. The sample size is set at 100 respondents, using probability sampling techniques and simple random sampling method. The data used is primary data collected through a digital questionnaire using Google Forms with a Likert scale. Data analysis was conducted with the assistance of SPSS 30 software. The results of the t-test show that hedonistic lifestyle has a positive and significant effect on impulsive buying behavior, flash sales have a positive and significant impact on impulsive buying behavior, while e-payment has a negative and insignificant effect on impulsive buying behavior and the F-test results indicate that hedonistic lifestyle, flash sales, and e-payment together have a positive and significant effect on buying behavior.